Secure offline superdistribution for mobile platforms. (1st September 2009) - Wolf, Marko; Osterhues, Andre; Stueble, Christian
Superdistribution and other peer-to-peer (P2P) distribution schemes like sharing or rental offer a flexible and user-friendly way to distribute digital content. However, the parties involved have different interests (e.g. user privacy vs. license enforcement) that should be reflected in the underlying security architecture. We identify characteristic P2P scenarios and demonstrate how these can be realised by applying a few basic licensing operations. We then present a security architecture to realise these basic license operations (1) in a generalised fashion and (2) employing the ARM TrustZone technology, which will be used in many future mobile platforms. Further, we extend existing superdistribution schemes for offline application, allowing a mobile peer to access superdistributed content without the need to first contact the actual licenser.